To solve the equation 6c - 5 = 1/2(6 + 4c), we can start by distributing the 1/2 to the terms inside the parentheses.
6c - 5 = 1/2 * 6 + 1/2 * 4c
Simplifying further, we have:
6c - 5 = 3 + 2c
Next, we want to isolate the variable c on one side of the equation. We can do this by subtracting 2c from both sides:
6c - 2c - 5 = 3
Combining like terms:
4c - 5 = 3
Now, we can isolate the constant term by adding 5 to both sides:
4c - 5 + 5 = 3 + 5
=> 4c = 8
Finally, divide both sides of the equation by 4 to solve for c:
4c/4 = 8/4
=> c = 2
Therefore, the solution to the equation 6c - 5 = 1/2(6 + 4c) is c = 2.
6c-5=1/2(6+4c)
1 answer